PECULIARITIES OF ORGANIZATION OF MANDATORY EVACUATION OF A CERTAIN CATEGORY OF POPULATION BY RAILWAY BY THE NATIONAL GUARD OF UKRAINE - Golubok, Maksym; Zhabinskiy, Volodymyr (Honor and Law, 2022)
The article considers peculiarities of organization and planning of mandatory evacuation of a certain category of population by railway in the case of emergency and martial law by the National Guard of Ukraine. The analysis of the available special cars of type «ZAK», which are on the balance of «Ukrzaliznytsia» has been carried out. Specific characteristics of moving a certain category of population, during mandatory evacuation taking into account the observance of keeping the rules have been determined. The procedure of preparation of echelon guards of the National Guard of Ukraine for the obligatory evacuation of a separate category of population is determined. Scenarios of actions during the mandatory evacuation of a certain category of population were developed, depending on the operational situation. The calculation of the required number of cars and their types is carried out with the calculation of 100 persons of a separate category of population for each scenario of actions during the mandatory evacuation. The procedure of forming the echelons for carrying out mandatory evacuation of a separate category of population in the case of emergency and martial law by the National Guard of Ukraine with the use of the closed freight wagons with additional equipment has been suggested. The proposed version of the scheme of formation of the echelon and the requirements to its performing are formulated. Further scientific research within the framework of this scientific direction has been defined.